Molecular Docking: Bioactive Compounds in Indramayu Mango (Mangifera indica L.) Peel Waste as NS5B Hepatitis C Virus (HCV) Inhibitor - Gusnia Meilin Gholam; Mustika Luthfia; Iman Akhyar Firdausy (Universitas Airlangga, 2023)
Background: Hepatitis C is caused by hepatitis C virus (HCV) infection. HCV infection is one of the biggest causes of chronic liver disease. About 60-80% of patients with acute hepatitis C will develop chronic hepatitis C. Objective: This study aimed to analyze the potential of mango peel compounds as HCV NS5B inhibitors. Methods: The methods in this study are ligand preparation, physicochemical and pharmacokinetic predictions, protein structure preparation, molecular docking, data analysis, and visualization. Results: The results showed that the test ligands had binding free energies close to the reference ligands, namely Mangiferin -7.862 kcal/mol and respectively D-(+)-Maltose -6.453 kcal/mol, Dibutyl – phthalate -6.326 kcal/mol, bis-β-D-fructofuranose 1,2':2,3'-dianhydride -6.249 kcal/mol, 16-Heptadecyne-1,2,4-triol -5.476 kcal/mol, 3,4,5-trihydroxycyclohex-1-ene-1-carboxylic acid -5,360 kcal/mol, Trigonelline -4.905 kcal/mol, Hexitol -4.552 kcal/mol, α-Glucoheptitol -4.403 kcal/mol. All the test ligands bind the NS5B active site with hydrogen bonds. Furthermore, the ligand-receptor complex has a dissociation constant value and hydrogen bond length. Conclusion: The results showed that Mangiferin was the most potential ligand in inhibiting NS5B HCV of all the test ligands used.